2017
DOI: 10.2147/imcrj.s148712
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of fovea toward optic disk after macular hole surgery with internal limiting membrane peeling

Abstract: PurposeThe purpose of this study was to demonstrate a displacement of the foveal depression toward the optic disk after idiopathic macular hole (MH) surgery with internal limiting membrane (ILM) peeling.MethodsTwo patients with a unilateral MH developed an MH in the fellow eyes. Vitrectomy with ILM peeling was performed on the fellow eye to close the MH. Images of spectral-domain optical coherence tomography (SD-OCT) were used to measure the disk-to-fovea distances pre MH formation, after MH formation, and 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Anatomical migration after MH surgery was reported recently [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Fundus photography and OCT revealed that the fovea was displaced to the optic disc following MH closure via vitrectomy with ILM peeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomical migration after MH surgery was reported recently [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Fundus photography and OCT revealed that the fovea was displaced to the optic disc following MH closure via vitrectomy with ILM peeling.…”
Section: Introductionmentioning
confidence: 99%
“…The center of the MH is a landmark for measuring the movement of the retina after surgery; therefore, it is crucial to identify it with high accuracy and reproducibility. However, at present, the center of the MH is mostly identified manually [ 9 , 10 , 11 , 12 , 13 ]. Therefore, we investigated whether it is feasible to determine MH center using an automated image analysis technique.…”
Section: Introductionmentioning
confidence: 99%
“…All the previous reports[ 1 2 3 4 5 6 ] have reported a nasal shift with the temporal retina being more relaxed as a possible explanation. We saw that there is a temporal shift in 25% of the eyes and hence there may be other unknown factors in the postoperative remodeling process.…”
Section: Discussionmentioning
confidence: 96%
“…[ 4 ] Ohta et al . [ 5 ] compared the site of the pre-opened MH with the center of the opened hole and the postoperative closed hole. It would be interesting to see if the center shifts upon hole opening towards the side with the longer or shorter segment and how it affects the postoperative shift of the closed hole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation